PENGEMBANGAN LEMBAR KERJA SISWA UNTUK PRAKTIKUM KOROSI LOGAM DI SMA MENGGUNAKAN MODEL SIKLUS BELAJAR 7E - Wahidah, Gia Juniar Nur (2013)
The research aims to produce student work sheet for metal corrosion practicum in high school using 7E learning cycle model. Student work sheet that was developed consists of two titles, those are 'the factors that cause corrosion' and 'corrosion as an electrochemical process'. This research was a research development, and product developed was student work sheet for practicum. In general, initial analysis product phase performed as initial data sources to develop student work sheet. Based on the optimization lab procedures which was performed at this stage of product development was found that the iron corrosion requires the presence of oxygen and water. The process of corrosion was accelerated in the presence of an electrolyte solution with optimum conditions was obtained in NaCl 0.5 M. In the stages of product trial was conducted work sheet's test development to 29 high school students. The test results of product development in the school in the form of observations show that both procedures in student work sheet one and student work sheet two could be done by the students very well with the level of achievement 95% and 98% for each. This was supported by the positive response of students to the practical implementation of the student work sheet, and response is considered to be very good for student work sheet one is equal to 80% and good for the student work sheet two by 73%. In general, the teacher gave a positive response to both the student work sheet. Keywords: student work sheet, practicum, 7E learning cycle, corrosion Tujuan penelitian yang dilakukan adalah menghasilkan lembar kerja siswa untuk praktikum korosi logam di SMA menggunakan model siklus belajar 7E. LKS yang dikembangkan terdiri dari dua judul, yaitu 'faktor-faktor penyebab korosi' dan 'korosi sebagai proses elektrokimia'. Penelitian yang dilakukan merupakan penelitian pengembangan, dan produk yang dikembangkan adalah LKS praktikum. Secara umum, tahap analisis awal produk dilakukan sebagai sumber data awal untuk mengembangkan LKS. Berdasarkan optimasi prosedur praktikum yang dilakukan pada tahap pengembangan produk didapat bahwa korosi besi memerlukan adanya oksigen dan air. Proses korosi dipercepat dengan adanya larutan elektrolit dengan kondisi optimum diperoleh pada larutan NaCl 0,5 M. Pada tahap uji coba produk dilakukan uji pengembangan LKS terhadap 29 siswa SMA. Hasil uji pengembangan berupa observasi di sekolah menunjukkan bahwa kedua prosedur di LKS-1 dan LKS-2 dapat dilaksanakan oleh siswa dengan sangat baik yaitu dengan tingkat keterlaksanaan masing-masing 95 % dan 98%. Hal ini didukung dengan respon positif siswa terhadap LKS dan pelaksanaan praktikum yang dinilai sangat baik untuk LKS-1 yakni sebesar 80% dan baik untuk LKS-2 yakni sebesar 73%. Secara umum guru memberikan tanggapan positif terhadap kedua LKS praktikum tersebut. Kata kunci : LKS, praktikum, siklus belajar 7E, korosi